The bacterial community of entomophilic nematodes and host beetles. Issue 10 (20th April 2016) - Koneru, Sneha L.; Salinas, Heilly; Flores, Gilberto E.; Hong, Ray L.
Abstract: Insects form the most species‐rich lineage of Eukaryotes and each is a potential host for organisms from multiple phyla, including fungi, protozoa, mites, bacteria and nematodes. In particular, beetles are known to be associated with distinct bacterial communities and entomophilic nematodes. While entomopathogenic nematodes require symbiotic bacteria to kill and reproduce inside their insect hosts, the microbial ecology that facilitates other types of nematode–insect associations is largely unknown. To illuminate detailed patterns of the tritrophic beetle–nematode–bacteria relationship, we surveyed the nematode infestation profiles of scarab beetles in the greater Los Angeles area over a five‐year period and found distinct nematode infestation patterns for certain beetle hosts. Over a single season, we characterized the bacterial communities of beetles and their associated nematodes using high‐throughput sequencing of the 16S rRNA gene. We found significant differences in bacterial community composition among the five prevalent beetle host species, independent of geographical origin. Anaerobes Synergistaceae and sulphate‐reducing Desulfovibrionaceae were most abundant in Amblonoxia beetles, while Enterobacteriaceae and Lachnospiraceae were common in Cyclocephala beetles. Unlike entomopathogenic nematodes that carry bacterial symbionts, insect‐associated nematodes do not alter the beetles' native bacterial communities, nor do their microbiomes differ according to nematode or beetle host species. The conservation of Diplogastrid nematodes associations with Melolonthinae beetles and sulphate‐reducing bacteria suggests a possible link between beetle–bacterial communities and their associated nematodes. Our results establish a starting point towards understanding the dynamic interactions between soil macroinvertebrates and their microbiota in a highly accessible urban environment.